Ctenomys brasiliensis Blainville (Rodentia: Ctenomyidae): clarifying the geographic placement of the type species of the genus Ctenomys - Fernandes, Fabiano Araujo; Fornel, Rodrigo; Freitas, Thales R. O. (Zootaxa, 2012)
The genus Ctenomys (Rodentia: Ctenomyidae) comprises more than 60 species of subterranean rodents. Despite the widedistribution of the genus in southern America, the type locality of the type species—Ctenomys brasiliensisBlainville—was long thought to be the State of Minas Gerais in southeastern Brazil, well outside the presently knowndistributional area of the genus. Since it has never been collected again in that State, the type locality of this species is stilla matter for investigation. In order to elucidate this question, we investigated the skull of the type specimens of C.brasiliensis. From geometric morphometrics comparisons with other species of the genus, and taking into account thelabel information, it was possible to rediscover the type locality of this species. There is no doubt that the specimen wascollected in Minas, in the department of Lavalleja, Uruguay. Nowadays in this area on the southern coast of Uruguay, onlypopulations of Ctenomys pearsoni Lessa and Langguth were recognized. We suggest that more studies must be done tobetter understand the taxonomic relation between C. pearsoni complex and the C. brasiliensis, the type species for the genus that was collected in Uruguay and never occurred in southeastern Brazil.